Unified Deep Architectures for Real-Time Object Detection and Semantic Reasoning in Autonomous Vehicles - Aher, Vishal; Jondhale, Satish; Agarkar, Balasaheb; Chaudhari, Sachin (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2025)
The development of autonomous vehicles (AVs) has revolutionized the transportation industry, promising to boost mobility, lessen traffic, and increase safety on roads. However, the complexity of the driving environment and the requirement for real-time processing of vast amounts of sensor data present serious difficulties for AV systems. Various computer vision approaches, such as object detection, lane detection, and traffic sign recognition, have been investigated by researchers in order to overcome these issues. This research presents an integrated approach to autonomous vehicle perception, combining real-time object detection, semantic segmentation, and classification within a unified deep learning architecture. Our approach leverages the strengths of existing frameworks, including MultiNet’s real-time semantic reasoning capabilities, the fast-encoding methods of PointPillars to identify objects from point clouds, as well as the reliable one-stage monocular 3D object detection system. The offered model tries to improve computational efficiency and accuracy by utilizing a shared encoder and task-specific decoders that perform classification, detection, and segmentation concurrently. The architecture is evaluated against challenging datasets, illustrating outstanding achievements in terms of speed and accuracy, suitable for real-time applications in autonomous driving. This integration promises significant advancements in the perception systems of autonomous vehicles a providing in-depth knowledge of the vehicle’s environment through efficient concepts of deep learning techniques. In our model, we used Yolov8, MultiNet, and during training got accuracy 93.5%, precision 92.7 %, recall 82.1% and mAP 72.9%.